Profissão docente: visões de licenciandos de ciências biológicas em diferentes contextos - Fernanda Reis de Pinho Tavares (2007)
Teacher education has been intensively investigated. In parallel, there was a great development in the study of processes of teaching and learning at schools with a growing recognition of the importance of discursive interaction. However, we know little about these processes when we turn our attention to teacher education. This study aims to characterize the views of preservice teachers about their profession in two distinct contexts: in a classroom of student teaching and during individual interviews. The research took place in a discipline in which prospective biology teachers have their first formal contact with school context. This is a key discipline in preservice teacher education because it represents a moment where both academic and school experiences occur. First, we try to identify and describe the conceptions about teacher profession and teacher work in the classroom context. Furthermore, we intend to differentiate these conceptions about teacher profession and teacher work in different contexts. We mapand describe the central ideas present in a classroom interaction episode and in the individual interviews. To do that, we define and create makers to identify the kind of discourse interaction that we are looking for the argumentative discourse. The description of teacher conceptions in these distinct contexts was elaborated based on the analyses of classroom interaction episode and in the individual interviews. This analyses involved identifying central ideas from prospective teachers and the teacher educator. Moreover, we examine the classroom episode from the perspective of authors that adopted an argumentation framework- Billig (1987), McKerrow (1990) e Kuhn (1992). In the individual interviews, the conception of teacher as knower was identified. Teacher devaluation was identified in both contexts, interviews and classroom interaction. The discussion accosts this references teacher knowledge, professional development and teacher identity.